2020
DOI: 10.1155/2020/8647837
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Hemoglobin Association with Long-Term Outcomes of ST-Elevation Myocardial Infarction Patients Undergoing Primary Percutaneous Coronary Intervention

Abstract: Background. Anemia following acute myocardial infarction (AMI) is associated with poor outcomes. While previous studies in patients with AMI have focused on anemia at admission, we hypothesized that hemoglobin (Hb) decline during hospitalization and lower discharge Hb would be associated with greater long-term mortality in patients undergoing primary percutaneous coronary intervention (PCI) for ST-segment elevation myocardial infarction (STEMI). Methods. We analyzed records of 983 STEMI patients who were treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
3
4
0
Order By: Relevance
“…Few studies have looked into discharge Hb and long-term outcomes. Gao et al reported that 2-year all-cause mortality increased in patients who underwent PCI and had lower discharge Hb [36]. Their bleeding events rate was comparable to ours with 16.4% of patients having TIMI bleeding events, though no significant gastrointestinal bleeding and cerebral hemorrhage were reported [36].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Few studies have looked into discharge Hb and long-term outcomes. Gao et al reported that 2-year all-cause mortality increased in patients who underwent PCI and had lower discharge Hb [36]. Their bleeding events rate was comparable to ours with 16.4% of patients having TIMI bleeding events, though no significant gastrointestinal bleeding and cerebral hemorrhage were reported [36].…”
Section: Discussionsupporting
confidence: 77%
“…Gao et al reported that 2-year all-cause mortality increased in patients who underwent PCI and had lower discharge Hb [36]. Their bleeding events rate was comparable to ours with 16.4% of patients having TIMI bleeding events, though no significant gastrointestinal bleeding and cerebral hemorrhage were reported [36]. Other studies have not shown an association between discharge Hb and medium-term survival in patients who underwent CABG [37].…”
Section: Discussionsupporting
confidence: 74%
“… 18 , 19 Hemoglobin levels at admission have been reported to be associated with cardiovascular outcomes in patients with ST-segment elevation myocardial infarction (STEMI), with lower levels associated with an increased risk of adverse events, including LVR. 20 , 21 Our study further supports the importance of these factors in predicting LVR, which may help clinicians identify high-risk patients and optimize their management.…”
Section: Discussionsupporting
confidence: 70%
“…Anemia might be a risk factor for adverse events in many cardiovascular conditions, such as heart failure, 13,14 CAD after acute coronary syndrome 15 or percutaneous coronary intervention (PCI), especially when the patient requires antiplatelet medication 16 . It might also increase the risk of bleeding complication.…”
Section: Discussionmentioning
confidence: 99%